UNSTEADY MHD HEAT AND MASS TRANSFER FLOW OF A RADIATING FLUID PAST AN ACCELERATED INCLINED POROUS PLATE WITH HALL CURRENT - Sivaiah, G.; Reddy, K. Jayarami (International Journal of Research -GRANTHAALAYAH, 2017)
In this paper an analysis has been performed to study the effects of Hall current and radiation of MHD free convective heat and mass transfer flow of a radiating fluid past an accelerated inclined porous plate with hall current in presence of thermal diffusion and heat source. The solutions for velocity, temperature and concentration distributions are obtained by using Laplace transform technique. The expressions for skin friction, Nusselt number and Sherwood number are also derived. The variations in fluid velocity, temperature and species concentration are shown graphically, whereas numerical values of skin friction, Nusselt number and Sherwood number are presented in tabular form for various values of physical parameters.